2019
DOI: 10.1108/dlp-05-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Digital information resources: use and perceptions of deaf and hearing students

Abstract: Purpose The purpose of this study is to investigate the use of the internet among deaf and hearing students. The study also explores the perceptions of students toward the internet, online databases and digital libraries. Design/methodology/approach The study uses a survey questionnaire to collect data from the sample. The sample consists of 59 hearing and 53 deaf students studying at Al Ain University of Science and Technology Al Ain University (AAU). Descriptive statistics and t-tests are used to analyze d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In line with prior studies [10], high use of the Internet for educational purpose is reported for self-learning or teaching, accessing information related to the programs, improving thinking skills, and for improving knowledge. The results reflect the importance of the Internet for deaf students.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In line with prior studies [10], high use of the Internet for educational purpose is reported for self-learning or teaching, accessing information related to the programs, improving thinking skills, and for improving knowledge. The results reflect the importance of the Internet for deaf students.…”
Section: Discussionsupporting
confidence: 82%
“…Certainly, deaf people have the ability to learn and use ICT tools and resources for education, employment, and social interactions. They use digital information resources for reading, writing and social interaction, through their visual sense and auditory residues [9,10,11]. Prior studies have investigated the use of ICT tools and resources among deaf people from a different part of the world.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deafness is a low incidence disability (less than 5% of the school population) ( Noble, 2010 ). Colleges and universities are not typically prepared for supporting deaf students; so, their specific needs are not well understood ( Kaba and Ellala, 2019 ). The lack of understanding is not for want of intent; it is simply a lack of experience on the part of the Student Services department and the professors.…”
Section: Introductionmentioning
confidence: 99%